2022
DOI: 10.3389/fnins.2022.985709
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning-based self-induced emotion recognition using EEG

Abstract: Emotion recognition from electroencephalogram (EEG) signals requires accurate and efficient signal processing and feature extraction. Deep learning technology has enabled the automatic extraction of raw EEG signal features that contribute to classifying emotions more accurately. Despite such advances, classification of emotions from EEG signals, especially recorded during recalling specific memories or imagining emotional situations has not yet been investigated. In addition, high-density EEG signal classifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
1
2
0
Order By: Relevance
“…Although the direct connection to music might not be as apparent as in other brain areas, it is still worth further exploration. In our study, the results of the ECA module revealed the importance of high-frequency bands (beta and gamma) in distinguishing music composition states, similar to findings in emotional recognition research [ 45 , 49 , 50 ], where high-frequency bands performed slightly better than low-frequency bands (theta and alpha). This result emphasizes the close association between music and emotions, as well as the significant driving role of emotions in music composition and experience.…”
Section: Discussionsupporting
confidence: 88%
“…Although the direct connection to music might not be as apparent as in other brain areas, it is still worth further exploration. In our study, the results of the ECA module revealed the importance of high-frequency bands (beta and gamma) in distinguishing music composition states, similar to findings in emotional recognition research [ 45 , 49 , 50 ], where high-frequency bands performed slightly better than low-frequency bands (theta and alpha). This result emphasizes the close association between music and emotions, as well as the significant driving role of emotions in music composition and experience.…”
Section: Discussionsupporting
confidence: 88%
“…Recent studies (Ji and Dong, 2022;Li Z. et al, 2022;Xiao et al, 2022) have highlighted the neural networks in emotion recognition. These networks are capable of learning high-level features from raw EEG data in an incremental manner, which eliminates the requirement for feature extraction.…”
Section: Classification Methodsmentioning
confidence: 99%
“…With the development of technology, deep learning techniques were also heavily applied to EEG signal emotion recognition [ [19] , [20] , [21] ]. Zhong P et al [ 22 ] proposed a method based on regularized graph neural networks (RGNN) for emotion recognition of EEG, which accuracy was 94.24 % on the SEED dataset.…”
Section: Introductionmentioning
confidence: 99%